PEMETAAN POTENSI DAERAH DAN PENDAMPINGAN STRATEGI PEMASARAN UMKM DESA SUNGIWETAN - Subagio, Dyajeng Puteri Woro (STIE Pelita Nusantara, 2023)
The potential of a region is an important aspect that the Village Government should focus on, with one of its primary objectives being the welfare of the community. The development of a village can be observed through its social and economic resources, as well as its ability to manage them. Sungiwetan Village has encountered challenges in mapping its regional potential. Consequently, the products originating from Sungiwetan remain underexposed and unknown to the wider community. Moreover, there are several untapped and underdeveloped regional potentials. Therefore, the community engagement team from Unmer Pasuruan, in agreement with the target beneficiaries of this program, including the Village Government, village chiefs, the head of the Village-Owned Enterprises (BUMDes), and small and medium-sized enterprises (SMEs) participants in the Focus Group Discussion (FGD), has initiated a program for mapping, profiling, and supporting the marketing of Sungiwetan's regional potential. This program is executed through five methods: 1) Preparation phase, 2) Data collection and profiling of SMEs, 3) Socialization of marketing strategies and product innovation mentoring, 4) The creation of a catalog and map of Sungiwetan Village's regional potential, and 5) Evaluation. The program has been successfully implemented, as evidenced by the accomplishments, including the SME catalog of Sungiwetan Village, the regional potential map, product innovations, and the enhanced understanding of product strategies, promotion, and digital marketing among SME participants. Keywords: regional potential, marketing strategy, SME catalog, regional potential map.